Law & punishment pertaining to marital rape: a comparative study between Malaysia and California / Nurul Amirah Mohamad Nasir, Siti Munirah Ismail and Farhana Zahari - Mohamad Nasir, Nurul Amirah; Ismail, Siti Munirah; Zahari, Farhana (2014)
This research is aim to provide a better view and enforcement of the law on marital rape in Malaysia by making some review on the law at hand with those in California. This research is motivated as the law pertaining to marital rape in Malaysia is not yet effectively prosecuted as a crime. This research deals with few issues such as from the wording of the Section in Penal code pertaining to the law involved, the differentiation of the law with domestic violence, and the punishment. A different perspective is viewed to complete the research and analysis has been made by referring to Penal Code Act 574 and California Penal Code. The finding of research is included at the end of the chapter in this research.